(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
This paper presents the results of chemical analysis of seven selected nutrient elements in soil samples collected from four pedons representing four extensive benchmark soil series from the Ganges river floodplain of Bangladesh. The results of total and available N, P and K contents as well as DTPA (diethelene-triamine pentaacetic acid) -extractable and total Fe, Mn, Cu and Zn contents in the soils were reported. With respect to nutrient status, the soils were rated as fertile with reasonably high production potential under balanced fertilization. The nutrient contents are presumed to be renewed every year by fresh siltation during the monsoon floods. High contents of total iron and potassium in these soils are noteworthy features. Iron in these paddy soils forms redoximorphic features. The release mechanism of K+ from the potash bearing minerals needs further study to determine the need for K fertilization in these soils. The total quantities of the seven studied nutrients in these soils vary widely. In the same way the quantities of extractable (available) nutrients in the soils vary widely. For elements like P, K and Fe less than one percent of the total remain in the available forms. Soil characteristics like organic matter, clay content, cation exchange capacity, pH and lime content have important roles in the availability of nutrients in soils. Keywords: Ganges floodplain, Benchmark soil, DTPA-extractable micronutrients, Soil characteristics DOI: 10.3329/bjsir.v44i3.4411 Bangladesh J. Sci. Ind. Res. 44(3), 359-366, 2009